The Systems Model of Creativity 2014
DOI: 10.1007/978-94-017-9085-7_16
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Regions Involved in the Generation of Musical Structures During Improvisation in Pianists

Abstract: Abstract& Studies on simple pseudorandom motor and cognitive tasks have shown that the dorsolateral prefrontal cortex and rostral premotor areas are involved in free response selection. We used functional magnetic resonance imaging to investigate whether these brain regions are also involved in free generation of responses in a more complex creative behavior: musical improvisation. Eleven professional pianists participated in the study. In one condition, Improvise, the pianist improvised on the basis of a visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 56 publications
2
47
0
1
Order By: Relevance
“…In line with this reasoning, it can be observed that our classical pianists activate a network including the pre-SMA, PMD and DLPFC, typically associated with explicit processing of novel motor sequences, while jazz pianists rely on regions for implicit routine and automated behavior, showing a more caudal distribution of activity in the SMA and PMD, in conjunction with activity in limbic regions and the basal ganglia (Doyon and Benali, 2005). Notably, all previous imaging studies on piano improvisation (Bengtsson et al, 2007;Berkowitz and Ansari, 2008;de Manzano and Ullen, 2012;Limb and Braun, 2008) as well as the present investigation, find that the PMD is involved in musical creativity.…”
Section: Free Generation Vs Sight Readingmentioning
confidence: 52%
See 3 more Smart Citations
“…In line with this reasoning, it can be observed that our classical pianists activate a network including the pre-SMA, PMD and DLPFC, typically associated with explicit processing of novel motor sequences, while jazz pianists rely on regions for implicit routine and automated behavior, showing a more caudal distribution of activity in the SMA and PMD, in conjunction with activity in limbic regions and the basal ganglia (Doyon and Benali, 2005). Notably, all previous imaging studies on piano improvisation (Bengtsson et al, 2007;Berkowitz and Ansari, 2008;de Manzano and Ullen, 2012;Limb and Braun, 2008) as well as the present investigation, find that the PMD is involved in musical creativity.…”
Section: Free Generation Vs Sight Readingmentioning
confidence: 52%
“…Thus, this is the third study (incl. Bengtsson et al, 2007;de Manzano and Ullen, 2012) in which improvisation is not accompanied by a deactivation of the dorsolateral prefrontal cortex, as reported by Limb and Braun (2008) during improvisation. In Limb and Braun (2008), improvisation was compared to execution of over-learned musical sequences at two levels of complexity.…”
Section: Free Generation Vs Sight Readingmentioning
confidence: 69%
See 2 more Smart Citations
“…Additionally, a recent study found that the premotor region was a critical region for goal-directed actions (Gremel and Costa, 2013). Other fMRI studies also indicated that the premotor cortex is involved in diverse creative activities (Bengtsson et al, 2007;Chávez-Eakle et al, 2007;Aziz-Zadeh et al, 2012). In addition, Mostofsky et al (2002) found that boys with attention-deficit/hyperactivity disorder (ADHD), which were known for being excessively impulsive, hyperactive and off-task (inattentive), had decreased volume in the premotor cortex.…”
Section: Neural Correlates Of Trait Creativity Scan (2015)mentioning
confidence: 99%